The Exacerbation of Lutembatcher Syndrome in The Setting of COVID-19 infection: A Rare Case Report - Yusuf Azmi; Fitriyani S. Laitupa; Adriyawan Widya Nugraha; Terrence T. E. Lusida; Lisca Namretta; Nida A. Suyani (Universitas Airlangga, 2022)
Lutembatcher syndrome is a rare cardiac condition characterized by a combination of the atrial septal defect (ASD; congenital or iatrogenic) and mitral stenosis (MS; congenital or acquired). Patients with Lutembatcher syndrome and adults with congenital heart disease (ACHD) in general may be at high risk when accompanied by coronavirus disease 2019 (COVID-19). Since there is no published study on the impact of COVID-19 on ACHD, little is known about management strategies in this subset of patients. Herein, we report a young adult female presented with abdominal discomfort, swollen legs, fever, cough, and dyspnea. The patient had developed palpitation and exercise intolerance five years ago but paid it no attention. Echocardiography revealed large secundum type ASD with severe MS (Wilkins score of eight) and a nasopharyngeal swab confirmed SARS-COV-2 infection. The patient was diagnosed with Lutembacher syndrome and COVID-19. Intensive treatment was given to relieve symptoms due to heart failure and to treat COVID-19 pneumonia. Patients with Lutembatcher syndrome are at a higher risk of being infected with COVID-19 and manifest into severe infections. Therefore, determining the risk of infection and the severity of COVID-19 in ACHD patients are required during the pandemic. Keywords: Adults with congenital heart disease, Coronavirus disease 2019, Lutembacher